Equilibrium and Isotherm Modeling of Toxic dye Adsorption onto Modified Apricot Stone - Abbas, M.; Aksil, T. (Algerian Journal of Research and Technology (AJRT), 2019)
In the present study, adsorption of toxic dye Diret red 28 (acidbenzidinediazo-bis-1-naphtylamine-4-sulfonique ) from aqueous solution was investigated using activated carbon synthesized with Phosphoric Acid activation. The synthesized adsorbent was analyzed using BET, FT-IR and SEM techniques. The BET analysis showed that the area provided by the synthesized activated carbon was 88.01 m2/g.The adsorption isotherms of Toxic dye onto ASAC are determined and correlated with common isotherms equations. The smaller RMSE values obtained for the Langmuir and Dubinin-R models indicate the better curves fitting, the monolayer adsorption capacity of toxic dye is found to be 32.85 mg/g at temperature 25 oC and 23.42 mg/g at temperature 65 oC at pH 13. The adsorption of toxic dye was carried out using a batch system and the effects of pH, contact time, adsorbent dosage, initial concentration and temperature on the adsorption capacity of synthesized adsorbent were investigated. Kinetics studies proved that for both metals, the kinetic data follows the pseudo second order kinetic model. In addition, the thermodynamics studies proved that the adsorption process of toxic dye could be considered spontaneous and endothermic.